Analisis Prioritas Pengelolaan Sampah Kampus Berdasarkan Persepsi Mahasiswa Pendidikan Biologi dengan Metode USG - Dian Ananda Silaban; Indah Juwita Sari (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2026)
This research aimed to analyze the priority of waste management problems in the campus environment based on the perceptions of Biology Education students using the Urgency, Seriousness, Growth (USG) method. A quantitative descriptive survey method was employed with a USG questionnaire instrument assessed through a four-level scale. The results showed that the highest priority problem was the lack of student awareness to bring their own drinking/eating containers (score 320), followed by littering behavior (score 319) and waste accumulation in strategic areas (score 314). The interpretation of the results indicated that student behavior aspects were crucial factors in campus waste management. This research concluded and recommended the need for an integrated strategy consisting of continuous education, provision of supporting facilities, and adjustment of waste container capacity and emptying frequency.